Clinical practice guideline for the diagnosis and management of acute and subacute low back pain for the Peruvian Social Security (EsSalud) - Carpio, Ricardo (2018)
Introduction. This article summarizes the clinical practice guide (CPG) for the diagnosis and management of acute and sub-acute low back pain in the Social Security of Peru (EsSalud). Objective. To provide clinical recommendations based on evidence for the diagnosis and management of acute and sub-acute low back pain in EsSalud. Methods. A CPG for the diagnosis and management of low-back pain in EsSalud was developed. To this end, a local guideline development group (local GDG) was established, including medical specialists and methodologists. The local GDG formulated 11 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and -when it was considered pertinent- primary studies were conducted in Pubmed, Embase and the Cochrane library during 2016. The evidence to answer each of the posed clinical questions was selected. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the local GDG used the GRADE methodology to review the evidence and formulate the recommendations and the flowcharts of diagnosis and treatment. Finally, the CPG was approved with Resolution N 43-IETSI-ESSALUD-2016. Results. This CPG addressed 11 clinical questions, divided into three topics: diagnosis (three questions), non-pharmacological treatment (four questions), and pharmacological treatment of low-back pain (four questions). Based on these questions, 12 recommendations (2 strong recommendations and 10 conditional recommendations), and 2 flowcharts were formulated. Conclusion. This article summarizes the methodology and evidence-based conclusions from the CPG for the diagnosis and management of low-back pain in EsSalud.